O discurso do movimento #OcupeOCocó e sua luta pela significação nas redes sociais - Luciana Correia Barbosa; Sérgio Carvalho Benício de Mello; Henrique Muzzio (Ciências Sociais Unisinos)
The purpose of this article is to analyze the speech #OcupeOCocó, a popular movement in defense of Coco Park, in Fortaleza (Brazil), which emerged on social networks in July 2013, and its struggle for meaning in social networks from posts and users’ comments on the official website of the movement on Facebook and its Twitter profile. We used the Discourse Theory proposed by Laclau and Mouffe (1985) in order to understand how this process of meaning takes place and how the elements fit together in the pursuit of hegemony of the content of its speeches when the discursive practices revealed a social antagonism in which disputes occur from the signification of a predatory development x sustainable development. Although the protesters were expelled from the site three months later, the movement speech continues to build new relationships and reveal new discursive practices in social networks.